Fluorinated vanadium phosphate magnesium battery positive electrode material as well as preparation method and application thereof
The fluorinated vanadium phosphate magnesium battery positive electrode material addresses slow ion diffusion and low voltage issues by enhancing ion transport and structural stability, achieving high capacity and long cycle life through optimized composition and synthesis methods.
Patent Information
- Application Number
- CN202411164034.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-23
AI Technical Summary
Existing magnesium-ion batteries face challenges with slow reversible intercalation and ion diffusion due to high charge density and strong solvation of magnesium ions, leading to limited operating voltage and energy density, and existing cathode materials suffer from poor crystallinity and cycle stability.
A fluorinated vanadium phosphate magnesium battery positive electrode material with a chemical composition of Mg a Na b V 2-x M x (PO 4 ) 3-y F y, where M is Fe, Ti, Cr, Ni, Cu, Mn, or Co, and specific particle sizes and morphologies, prepared through methods like high-energy ball milling, room temperature co-precipitation, or hydrothermal reactions, to enhance ion transport and structural stability.
The material achieves high operating voltage (up to 2.5V) and reversible specific capacity (up to 120mAh/g) with over 100 weeks of stable cycling, and is suitable for large-scale applications with a simple synthesis process.
Smart Images

Figure CN119133439A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage materials, and specifically relates to a fluorinated vanadium phosphate magnesium battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Magnesium-ion batteries have good air stability, smaller ion radius (0.072nm), lower reduction potential (-2.356V relative to standard hydrogen electrode) and higher volumetric capacity (3833mAh / cm 3 ), showing greater application potential than other types of post-lithium-ion battery technology. In addition, the reserves of magnesium in the earth's crust (2.3%) are 1045 times that of lithium (0.0022%), and the abundant magnesium resources make it have a lower production cost. Moreover, metallic magnesium is relatively stable in the air and is not easy to grow magnesium dendrites. The development of high-performance magnesium-ion battery large-scale energy storage technology is of great appeal.
[0003] However, the high charge density and strong solvation of magnesium ions lead to slow reversible intercalation and ion diffusion in the cathode material and at the solid-liquid interface, which seriously affects the electrochemical performance of magnesium ion batteries. -3 S / cm) and a three-dimensional open framework with a stable structure, for Mg 2+ Ion embedding provides sufficient lattice gaps with the advantages of high operating voltage and stable structure, but the operating voltage is very limited, affecting the overall energy density of magnesium-ion batteries.
[0004] CN202310598433.0 discloses a phosphate positive electrode material for a rechargeable magnesium battery, wherein the phosphate Mg x M 3-x (PO 4 ) 2 The preparation method can better combine the advantages of traditional solid phase method, sol-gel method and hydrothermal method to obtain a uniform phosphate precursor with a capacity of up to 141.8 mAh g in the three-electrode test. -1 , but its operating voltage is not high and its capacity retention rate is less than 80%.
[0005] CN202311786628.4 discloses silicate positive electrode material MgFeSiO 4 The preparation method and application thereof, using a simple and efficient electric Joule heating method, can achieve rapid preparation of the target product. The obtained positive electrode material can obtain good cycle stability, but the discharge specific capacity is only 62.6mAh g-1 and the material crystallinity is poor, which still has certain problems in practical application.
[0006] The development of polyanion positive electrode materials based on high operating voltage and high discharge capacity urgently needs breakthroughs. Summary of the invention
[0007] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, the main purpose of the present invention is to provide a fluorinated vanadium phosphate magnesium battery positive electrode material with high energy density and good cycle stability and a preparation method thereof.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] A fluorinated vanadium phosphate magnesium battery positive electrode material, the chemical composition of the fluorinated vanadium phosphate magnesium battery positive electrode material is: Mg a Na b V 2-x M x (PO 4 ) 3-y F y , wherein M is one or more of Fe, Ti, Cr, Ni, Cu, Mn, Co, and Nb, 0<a≤1.5, 0<b≤3, 0<x≤1.3, and 0<y≤3.
[0010] Furthermore, the particle size of the fluorinated vanadium phosphate magnesium positive electrode material is 0.1 μm to 20 μm, and the morphology is one of nanoparticles, micron spheres or micron block structures.
[0011] The present invention also provides a method for preparing a positive electrode material for a fluorinated vanadium phosphate magnesium battery, comprising the following steps:
[0012] 1) mixing raw materials of a vanadium source, a transition metal M source, a magnesium source, a sodium source and a fluorine source uniformly and performing a chemical reaction;
[0013] 2) After the reaction is completed, the product is washed and dried to obtain a fluorinated vanadium phosphate magnesium battery positive electrode material.
[0014] In some specific embodiments, the vanadium source includes any one of a trivalent vanadium source, a tetravalent vanadium source, and a pentavalent vanadium source, or a combination of at least two thereof;
[0015] The transition metal M source is one or more of an iron source, a titanium source, a chromium source, a nickel source, a copper source and a cobalt source;
[0016] The iron source is any one of ferrous fluoride, ferrous chloride, ferrous bromide, ferrous nitrate, ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous acetate, ferrous hydroxide, ferrous oxide, ferrous sulfide, ferrous acetylacetonate, ferrous trifluoride, ferric chloride, ferrous tribromide, ferric nitrate, ferric sulfate, ferrous carbonate, ferrous oxalate, ferric acetate, ferric hydroxide, ferrous oxide, ferrous tetroxide or ferrous acetylacetonate, or a combination of at least two thereof;
[0017] The titanium source is any one of titanium chloride, titanium bromide, titanium sulfate, titanium nitrate, titanium oxalate, titanium formate, titanium acetate, titanium dioxide, titanium acetylacetonate and tetrabutyl titanate, or a combination of at least two thereof;
[0018] The chromium source includes any one of chromium trichloride, chromium tribromide, chromium nitrate, chromium sulfate, chromium oxalate, chromium formate, chromium acetate, chromium chromate, chromium lactate, basic chromium sulfate, chromium perchlorate, chromium trioxide, chromium hydroxide, chromium acetylacetonate, sodium chromate and sodium dichromate, or a combination of at least two thereof;
[0019] The nickel source is any one of nickelous fluoride, nickelous chloride, nickelous bromide, nickelous nitrate, nickelous sulfate, nickelous carbonate, nickelous oxalate, nickelous acetate, nickelous hydroxide, nickelous oxide, nickelous sulfide and nickelous acetylacetonate, or a combination of at least two thereof;
[0020] The copper source is any one of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide and copper acetylacetonate, or a combination of at least two thereof;
[0021] The manganese source is any one of manganous fluoride, manganous chloride, manganous bromide, manganous nitrate, manganous sulfate, manganous carbonate, manganous oxalate, manganous acetate, manganous hydroxide, manganous oxide, manganous sulfide, manganous acetylacetonate, manganous trifluoride, manganous chloride, manganous tribromide, manganous nitrate, manganous sulfate, manganous carbonate, manganous oxalate, manganous acetate, manganous hydroxide, manganous trioxide, manganous dioxide and manganous acetylacetonate, or a combination of at least two thereof;
[0022] The cobalt source is any one of cobalt acetate, cobalt oxide, cobalt carbonate, cobalt nitrate and cobalt chloride, or a combination of at least two of them.
[0023] Further, the vanadium source includes any one of vanadium trichloride, vanadium tribromide, vanadium trioxide, vanadium acetylacetonate, vanadium oxychloride, vanadium oxy sulfate, vanadium oxalate, vanadium dioxide, vanadium acetylacetonate, vanadium oxytrichloride, sodium vanadate, sodium metavanadate, ammonium metavanadate, vanadium pentoxide, vanadium-titanium magnetite or metallurgical vanadium slag, or a combination of at least two thereof.
[0024] In certain specific embodiments, when the vanadium source and the transition metal source are in a high oxidation state, the reaction raw materials further include a reducing agent; the reducing agent is any one or more of ascorbic acid, oxalic acid, citric acid, charcoal and hydroxylamine hydrochloride.
[0025] In some specific embodiments, the molar ratio of vanadium, transition metal M, magnesium, sodium, phosphorus and fluorine in the fluorinated vanadium phosphate magnesium battery positive electrode material is 1: (0-1): (1-5): (1-5): (1-10): (0.5-8).
[0026] In certain specific embodiments, the magnesium source comprises any one of magnesium phosphate, magnesium hydrogen phosphate, magnesium fluoride, magnesium acetate, magnesium vanadate, magnesium bromide, magnesium chloride, magnesium carbonate or magnesium perchlorate, or a combination of at least two thereof;
[0027] The sodium source includes any one of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium fluoride, sodium acetate, sodium orthovanadate, sodium metavanadate, sodium bromide, sodium chloride or sodium carbonate, or a combination of at least two thereof;
[0028] The fluorine source includes any one of sodium fluoride, ammonium fluoride, potassium fluoride, magnesium fluoride, calcium fluoride, aluminum fluoride or lithium fluoride, or a combination of at least two of them.
[0029] In certain specific embodiments, the chemical reaction is one of a high-energy ball milling reaction, a room temperature co-precipitation reaction or a hydrothermal reaction.
[0030] When the high-energy ball milling method is used, the material has a nanoparticle structure with a particle size between 100-200nm; when the room temperature co-precipitation reaction is used, the product has a micron-sized spherical structure with a particle size between 10-15μm; when the hydrothermal reaction is used, the product has a micron-sized block structure with a particle size between 5-10μm.
[0031] In some specific embodiments, the washing and drying are as follows: the washing medium includes water and / or an organic solvent, and the washing times are 4 to 6 times; the drying temperature is 50 to 70° C., and the drying time is 3 to 6 hours.
[0032] Furthermore, the organic solvent is one or more of ethanol, acetone or N-methylpyrrolidone.
[0033] The purpose of the present invention is to provide the application of the fluorinated vanadium phosphate magnesium battery positive electrode material in magnesium ion positive electrode materials.
[0034] Compared with the prior art, the present invention has at least the following advantages:
[0035] 1) The fluorinated vanadium phosphate magnesium battery positive electrode material provided by the present invention has active magnesium ions that can be intercalated and deintercalated and fast ion transport channels, and has excellent electrochemical properties. The Mg element can not only provide active intercalation ions to improve the material's discharge specific capacity; the Na element can effectively stabilize the material's framework structure, thereby improving the material's cycle stability; the F element can effectively increase the reaction potential, thereby increasing the operating voltage. When the positive electrode material contains the three elements of Mg, Na and F at the same time, the three elements of Mg, Na and F have a good synergistic effect, and the three elements together can effectively improve the specific capacity, cycle stability and operating voltage of the phosphate positive electrode. The magnesium battery assembled from the fluorinated vanadium phosphate magnesium battery positive electrode material has an operating voltage of more than 2.3V, which is much higher than other types of magnesium battery positive electrode materials (sulfide: ~1.0V; oxide: ~1.5V), and the reversible specific capacity in the first week is as high as 120mAh / g, which can be stably cycled for more than 100 weeks;
[0036] 2) The preparation method of the fluorinated vanadium phosphate magnesium battery positive electrode material provided by the present invention uses raw materials that can be effectively synthesized under low energy consumption conditions, has a simple synthesis process, and is suitable for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.
[0038] Figure 1 The XRD diffraction pattern of the fluorinated vanadium phosphate magnesium battery positive electrode material provided in Example 1;
[0039] Figure 2 This is a SEM electron microscope image of the fluorinated vanadium phosphate magnesium battery positive electrode material provided in Example 1;
[0040] Figure 3 The first week charge and discharge curve of the battery prepared from the fluorinated vanadium phosphate magnesium battery positive electrode material provided in Example 1 at a rate of 0.5C;
[0041] Figure 4 This is a SEM electron microscope image of the fluorinated vanadium phosphate magnesium battery positive electrode material provided in Example 2;
[0042] Figure 5 This is a SEM electron microscope image of the fluorinated vanadium phosphate magnesium battery positive electrode material provided in Example 3. DETAILED DESCRIPTION
[0043] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0044] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0045] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0046] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0047] Example 1
[0048] This embodiment provides a method for preparing a positive electrode material for a magnesium fluoride vanadium phosphate battery, which comprises the following steps:
[0049] (1) Take 1mmol magnesium acetate, 1mmol sodium fluoride, 2mmol ammonium metavanadate, 2mmol sodium dihydrogen phosphate, and 3mmol hydroxylamine hydrochloride and dissolve them in 40mol deionized water. After fully dissolving, place them in a polytetrafluoroethylene liner. Put the polytetrafluoroethylene liner in a hydrothermal kettle and heat it to 120℃ at a rate of 5℃ / min. Keep it at this temperature for 10h and then cool it to room temperature with the furnace to obtain the target product MgNa(VOPO 4 ) 2 Suspension of F;
[0050] (2) The suspension in (1) was washed three times with deionized water and anhydrous ethanol alternately, and then dried at 60° C. for 5 h to obtain MgNa(VOPO 4 ) 2 F magnesium ion battery positive electrode material.
[0051] The present application tests the electrochemical performance of the fluorinated vanadium phosphate magnesium battery positive electrode material prepared in this embodiment, specifically:
[0052] The prepared MgNa(VOPO 4 ) 2 F powder is mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and the electrode plate is prepared by coating or dry method. The assembly of magnesium ion battery is carried out in a glove box with Ar atmosphere, with magnesium metal as the negative electrode plate, and bis(trifluoromethylsulfonyl)imide magnesium, aluminum chloride, magnesium chloride, bis(trifluoromethylsulfonyl)imide sodium dissolved in ethylene glycol dimethyl ether (DME) as the electrolyte, assembled into CR2032 button battery.
[0053] from Figure 1 It can be seen from the XRD results that the magnesium ion battery positive electrode material provided in Example 1 is a pure phase. Figure 2 It can be seen from the SEM results that the magnesium ion battery positive electrode material provided in Example 1 is a micron-sized block structure with a particle size of about 15 μm.
[0054] from Figure 3 It can be seen that within the voltage window of 0.5 to 3.2 V, the discharge capacity at 0.5C rate is 99 mAh g -1 , the operating voltage is 2.3V; the capacity retention rate is 81% after 100 cycles.
[0055] Example 2
[0056] This embodiment provides a method for preparing a positive electrode material for a magnesium fluoride vanadium phosphate battery, which comprises the following steps:
[0057] (1) 0.9 mmol magnesium oxalate, 1.5 mmol sodium acetate, 1 mmol sodium metavanadate, 1 mmol manganese acetate, 2 mmol concentrated phosphoric acid, and 3 mmol magnesium fluoride were placed in a ball mill. The ball mill was configured according to a mass ratio of reactants to ball milling beads of 1:20. The reaction was carried out in a three-dimensional ball mill for 5 hours to obtain a product containing the target product Mg. 0.9 Na 1.5 VMn(PO 4 ) 2 F 3 mixture of
[0058] (2) The mixture of (1) was washed with deionized water for 5 times, and then dried at 70°C for 6 hours to obtain Mg 0.9 Na 1.5 VMn(PO 4 ) 2 F 3 Magnesium ion battery positive electrode materials.
[0059] The present application tests the electrochemical performance of the fluorinated vanadium phosphate magnesium battery positive electrode material prepared in this embodiment, specifically:
[0060] The prepared Mg 0.9 Na 1.5 VMn(PO 4 ) 2 F 3The powder is mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and the electrode plate is prepared by coating or dry method. The magnesium ion battery is assembled in a glove box with Ar atmosphere, with magnesium metal as the negative electrode plate, and bis(trifluoromethylsulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and bis(trifluoromethylsulfonyl)imide sodium dissolved in ethylene glycol dimethyl ether (DME) as the electrolyte, assembled into a CR2032 button cell.
[0061] from Figure 4 It can be seen from the SEM results that the magnesium ion battery positive electrode material provided in Example 2 is a nanoparticle structure with a particle size of about 100 nm.
[0062] Electrochemical performance tests were conducted at a voltage window of 0.5 to 3.2 V and a rate of 0.5C. The first-week discharge capacity was 108 mAh g -1 , the operating voltage is 2.5V, and the capacity retention rate is 85% after 100 cycles. The specific performance is shown in Table 1.
[0063] Example 3
[0064] This embodiment provides a method for preparing a positive electrode material for a magnesium fluoride vanadium phosphate battery, which comprises the following steps:
[0065] (1) 0.6 mmol magnesium oxalate, 1.8 mmol sodium acetate, 0.8 mmol vanadium acetylacetonate, 0.7 mmol ferric acetate, 0.5 mmol manganese acetate, 2 mmol diammonium phosphate, and 3 mmol ammonium fluoride were dissolved in 60 ml of a mixed solution of acetone and water in a volume ratio of 1:2. After fully dissolved, the mixture was placed in a beaker and allowed to stand for 24 hours to obtain a suspension containing the target product;
[0066] (2) The suspension in (1) was washed alternately with water and acetone for 4 times, and then dried at 50°C for 4 hours to obtain Mg 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO 4 ) 2 F 3 Magnesium ion battery positive electrode materials.
[0067] The present application tests the electrochemical performance of the fluorinated vanadium phosphate magnesium battery positive electrode material prepared in this embodiment, specifically:
[0068] The prepared Mg 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO 4 )2 F 3 The powder is mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and the electrode plate is prepared by coating or dry method. The magnesium ion battery is assembled in a glove box with Ar atmosphere, with magnesium metal as the negative electrode plate, and bis(trifluoromethylsulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and bis(trifluoromethylsulfonyl)imide sodium dissolved in ethylene glycol dimethyl ether (DME) as the electrolyte, assembled into a CR2032 button cell.
[0069] from Figure 5 It can be seen from the SEM results that the magnesium ion battery positive electrode material provided in Example 3 is a micron spherical structure with a particle size of about 20 μm.
[0070] Electrochemical performance tests were conducted at a voltage window of 0.5 to 3.2 V and a rate of 0.5C. The first-week discharge capacity was 120 mAh g -1 , the operating voltage is 2.4V, and the capacity retention rate is 82% after 100 cycles. The specific performance is shown in Table 1.
[0071] Comparative Example 1
[0072] This comparative example provides a method for preparing a positive electrode material for a magnesium fluoride vanadium phosphate battery, which comprises the following steps:
[0073] (1) 3 mmol of sodium acetate, 0.8 mmol of vanadium acetylacetonate, 0.7 mmol of ferric acetate, 0.5 mmol of manganese acetate, 2 mmol of ammonium dihydrogen phosphate, and 3 mmol of ammonium fluoride were placed in a mixed solution of 60 ml of acetone and water in a volume ratio of 1:2, and after fully dissolved, placed in a beaker and allowed to stand for 24 hours to obtain a suspension containing the target product;
[0074] (2) The suspension in (1) was washed alternately with water and acetone for 4 times, and then dried at 50° C. for 4 hours to obtain Na 3 V 0.8 Fe 0.7 Mn 0.5 (PO 4 ) 2 F 3 Magnesium ion battery positive electrode materials.
[0075] The present application tests the electrochemical performance of the fluorinated vanadium phosphate magnesium battery positive electrode material prepared in this embodiment, specifically:
[0076] The prepared Na 3 V 0.8 Fe 0.7 Mn 0.5 (PO 4 ) 2 F3 The powder is mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and the electrode plate is prepared by coating or dry method. The magnesium ion battery is assembled in a glove box with Ar atmosphere, with magnesium metal as the negative electrode plate, and bis(trifluoromethylsulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and bis(trifluoromethylsulfonyl)imide sodium dissolved in ethylene glycol dimethyl ether (DME) as the electrolyte, assembled into a CR2032 button cell.
[0077] Electrochemical performance tests were conducted at a voltage window of 0.5 to 3.2 V and a rate of 0.5C. The first-week discharge capacity was 85 mAh g -1 , the operating voltage is 2.2V, and the capacity retention rate after 100 cycles is 52%. See Table 1 for specific performance.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing a positive electrode material for a magnesium fluoride vanadium phosphate battery, which comprises the following steps:
[0080] (1) 0.6 mmol magnesium acetate, 1.8 mmol sodium acetate, 0.8 mmol vanadium acetylacetonate, 0.7 mmol iron acetate, 0.5 mmol manganese acetate, and 3 mmol ammonium dihydrogen phosphate were placed in a mixed solution of 60 ml acetone and water in a volume ratio of 1:2, and after fully dissolved, placed in a beaker and allowed to stand for 20 hours to obtain a suspension containing the target product;
[0081] (2) The suspension in (1) was washed alternately with water and ethanol for 6 times, and then dried at 60° C. for 5 h to obtain Mg 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO 4 ) 3 Magnesium ion battery positive electrode materials.
[0082] The present application tests the electrochemical performance of the fluorinated vanadium phosphate magnesium battery positive electrode material prepared in this embodiment, specifically:
[0083] The prepared Mg 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO 4 ) 3The powder is mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and the electrode plate is prepared by coating or dry method. The magnesium ion battery is assembled in a glove box with Ar atmosphere, with magnesium metal as the negative electrode plate, and bis(trifluoromethylsulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and bis(trifluoromethylsulfonyl)imide sodium dissolved in ethylene glycol dimethyl ether (DME) as the electrolyte, assembled into a CR2032 button cell.
[0084] Electrochemical performance tests were conducted at a voltage window of 0.5 to 3.2 V and a rate of 0.5C. The first week discharge capacity was 90 mAh g -1 , the working voltage is 1.6V, and the capacity retention rate after 100 cycles is 56%. Specific performance is shown in Table 1.
[0085] Comparative Example 3
[0086] This comparative example provides a method for preparing a positive electrode material for a magnesium fluoride vanadium phosphate battery, which comprises the following steps:
[0087] (1) 1.5 mmol of magnesium acetate, 0.8 mmol of vanadium acetylacetonate, 0.7 mmol of ferric acetate, 0.5 mmol of manganese acetate, 2 mmol of ammonium dihydrogen phosphate, and 3 mmol of ammonium fluoride were placed in a mixed solution of 60 ml of acetone and water in a volume ratio of 1:2, and after fully dissolved, placed in a beaker and allowed to stand for 20 hours to obtain a suspension containing the target product;
[0088] (2) The suspension in (1) was washed alternately with water and ethanol for 6 times, and then dried at 60° C. for 5 h to obtain Mg 1.5 V 0.8 Fe 0.7 Mn 0.5 (PO 4 ) 2 F 3 Magnesium ion battery positive electrode materials.
[0089] The present application tests the electrochemical performance of the fluorinated vanadium phosphate magnesium battery positive electrode material prepared in this embodiment, specifically:
[0090] The prepared Mg 1.5 V 0.8 Fe 0.7 Mn 0.5 (PO 4 ) 2 F 3The powder is mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and the electrode plate is prepared by coating or dry method. The magnesium ion battery is assembled in a glove box with Ar atmosphere, with magnesium metal as the negative electrode plate, and bis(trifluoromethylsulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and bis(trifluoromethylsulfonyl)imide sodium dissolved in ethylene glycol dimethyl ether (DME) as the electrolyte, assembled into a CR2032 button cell.
[0091] Electrochemical performance tests were conducted at a voltage window of 0.5 to 3.2 V and a rate of 0.5C. The first week discharge capacity was 95 mAh g -1 , the working voltage is 2.1V, and the capacity retention rate after 100 cycles is 31%. The specific performance is shown in Table 1.
[0092] Comparative Example 4
[0093] This comparative example provides a method for preparing a positive electrode material for a magnesium fluoride vanadium phosphate battery, which comprises the following steps:
[0094] (1) 0.6 mmol of magnesium acetate, 1.8 mmol of sodium acetate, 0.5 mmol of vanadium acetylacetonate, 1.0 mmol of ferric acetate, 0.5 mmol of manganese acetate, 2 mmol of ammonium dihydrogen phosphate, and 3 mmol of ammonium fluoride were placed in a mixed solution of 60 ml of acetone and water in a volume ratio of 1:2, and after fully dissolved, placed in a beaker and allowed to stand for 20 hours to obtain a suspension containing the target product;
[0095] (2) The suspension in (1) was washed alternately with water and ethanol for 6 times, and then dried at 60° C. for 5 h to obtain Mg 0.6 Na 1.8 V 0.5 FeMn 0.5 (PO 4 ) 2 F 3 Magnesium ion battery positive electrode materials.
[0096] The present application tests the electrochemical performance of the fluorinated vanadium phosphate magnesium battery positive electrode material prepared in this embodiment, specifically:
[0097] The prepared Mg 0.6 Na 1.8 V 0.5 FeMn 0.5 (PO 4 ) 2 F 3The powder is mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and the electrode plate is prepared by coating or dry method. The magnesium ion battery is assembled in a glove box with Ar atmosphere, with magnesium metal as the negative electrode plate, and bis(trifluoromethylsulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and bis(trifluoromethylsulfonyl)imide sodium dissolved in ethylene glycol dimethyl ether (DME) as the electrolyte, assembled into a CR2032 button cell.
[0098] Electrochemical performance tests were conducted at a voltage window of 0.5 to 3.2 V and a rate of 0.5C. The first week discharge capacity was 98 mAh g -1 , the working voltage is 2.0V, and the capacity retention rate after 100 cycles is 57%. The specific performance is shown in Table 1.
[0099] Table 1 Electrochemical properties of fluorinated vanadium phosphate magnesium battery positive electrode materials of various embodiments and comparative examples
[0100]
[0101] According to the test results in Table 1:
[0102] From the data results of Examples 1-3, it can be seen that the introduction of different transition metals, differences in element ratios and preparation methods will cause the materials to exhibit differentiated operating voltages and capacities.
[0103] From the data results of Example 3 and Comparative Example 1, it can be seen that the absence of magnesium in the target positive electrode has little effect on the discharge capacity in the first cycle, and will cause the battery cycle performance to decay rapidly.
[0104] It can be seen from the data results of Example 3 and Comparative Example 2 that the absence of fluorine in the target positive electrode material will lead to lower operating voltage and capacity of the material, and extremely poor cycle retention rate of the battery.
[0105] It can be seen from the data results of Example 3 and Comparative Example 3 that the absence of sodium element in the target positive electrode will greatly reduce the material cycle performance.
[0106] From the data results of Example 3 and Comparative Example 4, it can be seen that a too low ratio of the M element (Fe+V) in the target positive electrode will lead to a decrease in the material cycle stability, that is, exceeding the x range will cause the material structure stability to decrease, which is not conducive to the electrochemical performance.
[0107] From the data results of Example 3 and Comparative Examples 1, 2, 3, and 4, it can be seen that the three elements Mg, Na, and F have a good synergistic effect, and the combined effect of the three can effectively improve the specific capacity, cycle stability, and operating voltage of the phosphate positive electrode.
[0108] In summary, the magnesium ion battery positive electrode material component provided by the present invention has excellent working voltage and charge and discharge capacity, the working voltage can reach 2.5V, and the battery stability is relatively high, and the capacity retention rate can reach more than 80% after 100 cycles at 0.5C.
[0109] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A fluorinated vanadium phosphate magnesium battery positive electrode material, characterized in that: The chemical composition of the fluorinated vanadium phosphate magnesium battery positive electrode material is: Mg a Na b V 2-x M x (PO4) 3-y F y , wherein M is one or more of Fe, Ti, Cr, Ni, Cu, Mn, Co, and Nb, 0<a≤1.5, 0<b≤3, 0<x≤1.3, and 0<y≤3.
2. The fluorinated vanadium phosphate magnesium battery positive electrode material according to claim 1, characterized in that: The particle size of the fluorinated vanadium phosphate magnesium positive electrode material is 0.1 μm to 20 μm, and the morphology is one of nanoparticles, micron spheres or micron block structures.
3. A method for preparing the positive electrode material of magnesium fluorinated vanadium phosphate battery according to claim 1 or 2, characterized in that: The steps include: 1) mixing raw materials of a vanadium source, a transition metal M source, a magnesium source, a sodium source and a fluorine source uniformly and performing a chemical reaction; 2) After the reaction is completed, the product is washed and dried to obtain a fluorinated vanadium phosphate magnesium battery positive electrode material.
4. The method for preparing the positive electrode material of magnesium fluorinated vanadium phosphate battery according to claim 3, characterized in that: The vanadium source includes any one of a trivalent vanadium source, a tetravalent vanadium source, and a pentavalent vanadium source, or a combination of at least two thereof; The transition metal M source is one or more of an iron source, a titanium source, a chromium source, a nickel source, a copper source and a cobalt source; The iron source is any one of ferrous fluoride, ferrous chloride, ferrous bromide, ferrous nitrate, ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous acetate, ferrous hydroxide, ferrous oxide, ferrous sulfide, ferrous acetylacetonate, ferrous trifluoride, ferric chloride, ferrous tribromide, ferric nitrate, ferric sulfate, ferrous carbonate, ferrous oxalate, ferric acetate, ferric hydroxide, ferrous oxide, ferrous tetroxide or ferrous acetylacetonate, or a combination of at least two thereof; The titanium source is any one of titanium chloride, titanium bromide, titanium sulfate, titanium nitrate, titanium oxalate, titanium formate, titanium acetate, titanium dioxide, titanium acetylacetonate and tetrabutyl titanate, or a combination of at least two thereof; The chromium source includes any one of chromium trichloride, chromium tribromide, chromium nitrate, chromium sulfate, chromium oxalate, chromium formate, chromium acetate, chromium chromate, chromium lactate, basic chromium sulfate, chromium perchlorate, chromium trioxide, chromium hydroxide, chromium acetylacetonate, sodium chromate and sodium dichromate, or a combination of at least two thereof; The nickel source is any one of nickelous fluoride, nickelous chloride, nickelous bromide, nickelous nitrate, nickelous sulfate, nickelous carbonate, nickelous oxalate, nickelous acetate, nickelous hydroxide, nickelous oxide, nickelous sulfide and nickelous acetylacetonate, or a combination of at least two thereof; The copper source is any one of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide and copper acetylacetonate, or a combination of at least two thereof; The manganese source is any one of manganous fluoride, manganous chloride, manganous bromide, manganous nitrate, manganous sulfate, manganous carbonate, manganous oxalate, manganous acetate, manganous hydroxide, manganous oxide, manganous sulfide, manganous acetylacetonate, manganous trifluoride, manganous chloride, manganous tribromide, manganous nitrate, manganous sulfate, manganous carbonate, manganous oxalate, manganous acetate, manganous hydroxide, manganous trioxide, manganous dioxide and manganous acetylacetonate, or a combination of at least two thereof; The cobalt source is any one of cobalt acetate, cobalt oxide, cobalt carbonate, cobalt nitrate and cobalt chloride, or a combination of at least two of them.
5. The method for preparing the positive electrode material of magnesium fluoride phosphate vanadium salt battery according to claim 4, characterized in that: When the vanadium source and the transition metal source are in a high oxidation state, the reaction raw materials further include a reducing agent; the reducing agent is any one or more of ascorbic acid, oxalic acid, citric acid, charcoal and hydroxylamine hydrochloride.
6. The method for preparing the positive electrode material of magnesium fluorinated vanadium phosphate battery according to claim 3, characterized in that: The molar ratio of vanadium, transition metal M, magnesium, sodium, phosphorus and fluorine in the fluorinated vanadium phosphate magnesium battery positive electrode material is 1: (0-1): (1-5): (1-5): (1-10): (0.5-8).
7. The method for preparing the positive electrode material of magnesium fluoride phosphate vanadium salt battery according to claim 3, characterized in that: The magnesium source includes any one of magnesium phosphate, magnesium hydrogen phosphate, magnesium fluoride, magnesium acetate, magnesium vanadate, magnesium bromide, magnesium chloride, magnesium carbonate or magnesium perchlorate, or a combination of at least two thereof; The sodium source includes any one of sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium fluoride, sodium acetate, sodium orthovanadate, sodium metavanadate, sodium bromide, sodium chloride or sodium carbonate, or a combination of at least two thereof; The fluorine source includes any one of sodium fluoride, ammonium fluoride, potassium fluoride, magnesium fluoride, calcium fluoride, aluminum fluoride or lithium fluoride, or a combination of at least two of them.
8. The method for preparing the positive electrode material of magnesium fluoride vanadium phosphate battery according to claim 3, characterized in that: The chemical reaction is one of a high-energy ball milling reaction, a room temperature coprecipitation reaction or a hydrothermal reaction.
9. The method for preparing the positive electrode material of magnesium fluorinated vanadium phosphate battery according to claim 8, characterized in that: The washing and drying are specifically as follows: the washing medium includes water and / or an organic solvent, and the washing times are 4 to 6 times; the drying temperature is 50 to 70° C., and the drying time is 3 to 6 hours.
10. Use of the fluorinated vanadium phosphate magnesium battery positive electrode material according to any one of claims 1 or 2, or the fluorinated vanadium phosphate magnesium battery positive electrode material prepared by the preparation method according to any one of claims 3 to 9 in magnesium ion positive electrode materials.
Citation Information
Patent Citations
Carbon-coated magnesium ion-doped modified sodium vanadium fluorophosphate positive electrode material and preparation method thereof
CN115719806A
